l-carvone decreases breast cancer cells adhesion, migration, and invasion by suppressing FAK activation - Lima, Lucas Trevisan França de; Ganzella, Fernando Augusto de Oliveira; Cardoso, Gabriela Casani; Pires, Verônica dos Santos; Chequin, Andressa; Santos, Giulia Luiza; Braun-Prado, Karin; Galindo, Claudia Martins; Braz Junior, Odair; Molento, Marcelo Beltrão; Acco, Alexandra; Adami, Eliana Rezende; et al. (Chemico-biological interactions, 2023)
Breast cancer is one of the most common types of cancer in the world and current therapeutic strategies present severe drawbacks. l-carvone (CRV), a monoterpene found in Mentha spicata (spearmint), has been reported to have potent anti-inflammatory activity. Here, we examined the role of CRV in breast cancer cell adhesion, migration and invasion in vitro and how this component could suppress the growth of Ehrlich carcinoma-bearing mice. In vivo, treatment with CRV significantly decreased tumor growth, increased tumor necrosis area, and reduced the expression of VEGF and HIF-1α in Ehrlich carcinoma-bearing mice. Furthermore, the anticancer efficacy of CRV was similar to currently used chemotherapy (Methotrexate), and the combination of CRV with MTX potentiated the chemotherapy effects. Further mechanistic investigation in vitro revealed that CRV modulates the interaction of breast cancer cells with the extracellular matrix (ECM) by disrupting focal adhesion, which was shown by scanning electron microscopy (SEM) and immunofluorescence. Moreover, CRV caused a decrease in β1-integrin expression and inhibited focal adhesion kinase (FAK) activation. FAK is one of the most important downstream activators of several metastatic processes, including MMP-2 mediated invasion and HIF-1α/VEGF angiogenesis stimulus, both of which were found to be reduced in MDA-MB-231 cells exposed to CRV. Our results provide new insight about targeting β1-integrin/FAK signaling pathway with CRV, which could be a new potential agent in the treatment of breast cancer. [Display omitted] •l-carvone exerts cytotoxic effects and decreases metastatic parameters in human breast cancer cells.•l-carvone inhibits the integrin/FAK signaling pathway, decreasing MMP-2-mediated invasion.•Combination of l-carvone and chemotherapy lead to increased efficacy in mice Ehrlich tumor model.•l-carvone might be used as a potential adjuvant in breast cancer therapy.